The Learning Syntax Through Edmodo in the Beginners Class - Sugito Sugito; Sri Mulyani Endang Susilowati; Hartono Hartono; Supartono Supartono (International Journal of Evaluation and Research in Education (IJERE), 2017)
Integrating ICT (Information and Communications Technology) in the learning process is a necessity for a teacher in welcoming the 21st century. Knowledge and modern technology require teachers to learn how to use the technology in their teaching. Edmodo application is a very useful technology product in the learning process. Successful use of Edmodo applications in learning is influenced by: (1) teacher factors that include education, length of teaching, age, gender, frequent training, openness of teachers in accessing information, teaching places (city or village), and participation in the organization teachers and pedagogic competencies of educators in delivering materials, (2) facilities and infrastructure factors: building, room, hardware, software, internet connection, infrastructure to school, and instruction on using Edmodo application (3) learner factors that include motivation, courage to explore using Edmodo, and frequency of use of Edmodo app.